The Implementation of Artificial Intelligence in STEM-Based Creative Learning in the Society 5.0 Era - Sari, Junia Melya; Purwanta, Edi (Universitas Islam Negeri Raden Intan Lampung, 2021)
This research aimed at utilizing artificial intelligence in STEM-based creative learning in the society 5.0 era. The researchers investigated how an educator can utilize artificial intelligence and optimize it into a STEM-based learning process. STEM stands for Science, Technology, Engineering, and Math. The United States initiated it to combine the four disciplines integrated into a problem-based learning method and everyday contextual events. Artificial intelligence is an intelligence added to a system managed in a scientific context. Artificial intelligence is created and put into a machine (computer) to do work like humans. Several fields that use artificial intelligence include expert systems, computer games (games), fuzzy logic, artificial neural networks, and robotics. The researchers employed the literature review or library research by reviewing the results of various studies and collecting data from assorted references and sources. In conclusion, implementing artificial intelligence in STEM-based creative learning can be an alternative for an educator in the learning process. Artificial intelligence (AI) is expected to help educators in the creative learning process by implementing long-life education and showing behavioral changes in a better direction cognitively, affectively, and psychometrically, especially in the era of society 5.0.